Did "Kin-based societies" Exist? On the (De)Construction of an Anthropological Concept - Zorica Ivanović (University of Belgrade, 2016)
Concept of a ‘kin-based society’ relies on the assumption that, in stateless societies, kinship served as a fundamental and sufficient principle of social and political organization. Developed within the evolutionary paradigm, this concept has acquired different forms during the discipline’s history, depending on the theoretical orientation of various anthropologists and their understanding of the notion of ‘kinship’. Speaking from significantly different theoretical positions, anthropologists ranging from Rivers to Malinowski and Radcliffe- Brown, to Evans-Pritchard, Fortes and Levi-Strauss, all maintained that kinship formed a basis of social organization, although they did not always agree on the definition of the concept and the type of kinship relations that had this special quality of integrating and organizing the whole of society. The debates were primarily about whether it was consanguinity or affinity that served as a fundamental factor of forming and reproducing social relations. As modern anthropology rejects the idea that kinship relations can form the basis for social, economic and political integration in any type of society, including those without the state, class or caste system, this article considers the assumptions underpinning the construction of the concept witch for long played such an important role in the discipline’s knowledge but later came to be seriously challenged.